Morphological characteristics of guinea pigs bronchus associated lymphoid tissue in the dynamics of experi mental ovalbumin -induced allergic inflammation - Popko, S. S.; Попко, Світлана Сергіївна (My University, 2021)
SUMMARY. The actual problem of modern medicine is the reaction of Bronchus associated lymphoid tissue in airways chronic allergic diseases, because the full functioning of the respiratory system depends on the state of its local immune system. The aim – to study morphological changes in Bronchus associated lymphoid tissue of guinea pigs in the dynamics of experimental ovalbumin-induced allergic inflammation. Material and Methods. We have studied the lung of 48 guinea pigs, using histological and morphometric methods, under conditions of experimental ovalbumin-induced allergic inflammation. To assess the structural and functional rearrangement of pulmonary lymphoid nodules, their diameter and number were determined. Results. We have shown that sensitization and allergization with ovalbumin leads to a significant structural and functional rearrangement of Bronchus associated lymphoid tissue of guinea pigs in the form of the elevation in their number and diameter. We found more pronounced morphological changes in the late period of development of allergic inflammation in peribronchial lymphoid nodules, confirmed by the maximum magnification factor – 2.6 (p*/**<0.001) of the diameter of peribronchial lymphoid nodules in the 4th experimental group compared to the control. Conclusions. Sensitization and inhalation with ovalbumin leads to structural reorganization of Bronchus associated lymphoid tissue of guinea pigs in the form of the elevation in their number and diameter, had the unidirectional staged character depending on localization of lymphoid nodules and the duration of the experiment and claimed proliferative changes in the cellular adaptive link of local lung immunity of guinea pigs in late period of allergic inflammatory process. РЕ ЗЮМЕ. Актуальною проблемою сучасної медицини є реакція лімфоїдної тканини, асоційованої з бронхами, при хронічних алергічних захворюваннях дихальних шляхів, адже саме від стану місцевої імунної системи легень залежить повноцінне функціонування тканин та клітин дихальної системи організму. Мета – вивчити морфологічні зміни лімфоїдної тканини, асоційованої з бронхами морських свинок, в динаміці експериментального овальбумін-індукованого алергічного запалення. Матеріал і методи. За допомогою гістологічного, морфометричного та статистичного методів вивчили легені 48 самців морської свинки в умовах експериментального овальбумін-індукованого алергічного запалення. Для визначення структурної та функціональної перебудови лімфоїдних вузликів легень визначали величину їх діаметра та їх кількість. Результати. Встановлено, що сенсибілізація та алергізація овальбуміном призводить до суттєвої структурнофункціональної перебудови лімфоїдної тканини, асоційованої з бронхами морської свинки, у вигляді збільшення їх кількості та розмірів. Найсуттєвіші зміни відбуваються протягом пізнього періоду розвитку алергічного запалення у перибронхіальних лімфоїдних вузликах, що підтверджує максимальний коефіцієнт збільшення – 2,6 (p*/**<0,001) діаметра перибронхіальних лімфоїдних вузликів в 4-ій експериментальній групі, порівняно з контролем. Висновки. Сенсибілізація та інгаляційна алергізація овальбуміном призводить до структурної реорганізації лімфоїдної тканини, асоційованої з бронхами морських свинок, у вигляді зростання їх кількості та розмірів, яка має односпрямований стадійний характер в залежності від локалізації лімфоїдних вузликів і тривалості експерименту та є проявом проліферативних змін клітинної адаптивної ланки місцевого імунітету легень морських свинок протягом пізнього періоду алергічного запального процесу.
Морфологічна характеристика лімфоїдної тканини, асоційованої з бронхами морських свинок , в динаміці експериментального овальбумін-індукованого алергічного запалення
Keywords: Bronchus associated lymphoid tissue; experimental allergic inflammation; ovalbumin; guinea pig; лімфоїдна тканина; асоційована з бронхами; експериментальне алергічне запалення; овальбумін; морська свинка